The coastal environmental profile of Singapore - Chia Lin Sien; Khan, Habibullah; Chou Loke Ming (Manila, Philippines ICLARM, 1988)
ICLARM Technical Reports; 21ICLARM Contribution No. 499Association of Southeast Asian Nations/United States Coastal Resources Management Project Technical Publications Series 3
Keywords: Environmental policy; Coastal zone management